Leader-member exchange, gender, and influence tactics. A test on multinational companies in Malaysia - Lo, May-Chiun; T., Ramayah; Ernest Cyril , de Run (Problems and Perspectives in Management, 2009)
Building upon the “social exchange theory” notion (Blau, 1964; Emerson, 1962), this paper hypothesized the direct impact of leader-member exchange on supervisors’ use of downward influence tactics. Leader-member exchange (LMX) and influence tactics were conceptualized as 2- and 3-dimensional constructs, respectively. One hundred and fifty-eight Malaysian managers and executives working in large scale multinational companies voluntarily participated in this study. Two dimensions of LMX, namely loyalty and affect, have direct relationships with soft influence tactics, whereas the moderating hypotheses were not found to have any significant impact on the dependent variables. The findings suggested that leader-member exchange would have moderate impact on supervisors’ use of influence tactics on their subordinates. Implications of the findings, potential limitations of the study, and directions for future research were discussed further.